2013
DOI: 10.1007/s00128-013-1128-y
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation and Residues of Difenoconazole and Azoxystrobin in Bananas and Soil in Two Agro-Climatic Zones of China

Abstract: Residues of a fungicide suspension (12 % difenoconazole, 18 % azoxystrobin) in bananas and soil were studied under tropical and subtropical monsoon climates, in Hainan and Yunnan provinces, respectively. The half-lives in bananas were shorter in Hainan (difenoconazole: 8.4-10.7 days; azoxystrobin: 7.8-8.4 days) than Yunnan (difenoconazole: 11.3-13.0 days; azoxystrobin: 10.4-11.6 days), possibly because of the higher temperatures and solar radiation levels in Hainan. The half-lives in soil were shorter in Yunna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 9 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…In China, nearly 333 000 hectares of land is earmarked for banana production, and the annual banana production is 9 million tonnes. 1 In China, bananas are grown mainly in tropical and subtropical regions such as the provinces of Hainan, Guangxi, Guangdong and Yunnan. The leaf spot disease caused by Mycosphaerella musicola Mulder is the most serious and destructive banana disease and damages almost 50% of banana cultures each year.…”
Section: Introductionmentioning
confidence: 99%
“…In China, nearly 333 000 hectares of land is earmarked for banana production, and the annual banana production is 9 million tonnes. 1 In China, bananas are grown mainly in tropical and subtropical regions such as the provinces of Hainan, Guangxi, Guangdong and Yunnan. The leaf spot disease caused by Mycosphaerella musicola Mulder is the most serious and destructive banana disease and damages almost 50% of banana cultures each year.…”
Section: Introductionmentioning
confidence: 99%
“…The fast degradation of azoxystrobin was confirmed by their study under field conditions. It was also suggested that azoxystrobin was stable in some matrices . The MRLs, a crucial parameter, are the safety indicators of pesticides in agricultural products.…”
Section: Resultsmentioning
confidence: 99%
“…It was also suggested that azoxystrobin was stable in some matrices. 7,29 The MRLs, a crucial parameter, are the safety indicators of pesticides in agricultural products. The MRLs established by the Codex, China, and the EU for azoxystrobin in cucumber are 0.1, 0.5, and 1.0 mg kg −1 .…”
Section: Residues Of Azoxystrobin and Meptyldinocap On Cucumbermentioning
confidence: 99%
“…In a greenhouse study, when the tomato leaves was sprayed with homogenous 0.1% aqueous solution of Amistar 250 SC, it was found that the t 1/2 of azoxystrobin was on the average within 13 days [2]. Huan et al found that the half-lives of the azoxystrobin in banana soil in Yunan province were shorter than in Hainan province, and the half-lives were 11.9-13.9 days and 16.0-16.1 days, respectively [21]. In the current study, the concentration of residues and the dissipation rate were analyzed under field conditions.…”
Section: Validation In Tomato and Soil Samples Under Field Conditionsmentioning
confidence: 99%